The enterprise’s external knowledge acquisition capability and technological diversification: From the perspective of intellectual property strategy - Chang, Ke-Chiun; Jiang, Yukun; Huang, Chengjing; Xiong, Xinyi; Chen, Ziyan; Lai, Yen-Chun; Chai, Kuang-Cheng (Frontiers in Psychology, 2023)
Enterprises need intellectual property rights to protect their core knowledge, and technological diversification is an important strategic measure for enterprises to improve innovation performance. From the perspective of external resource acquisition, this study explores the mechanism of external knowledge acquisition capability (internal absorptive capability and external relational learning) on firm’s technological diversification. It considers the impact of firm’s innovation capability and external environmental uncertainty. The survey data of 258 Chinese pharmaceutical companies were obtained through questionnaire surveys, and various theoretical hypotheses were validated using regression analysis methods. The results show that internal absorptive capacity, external relational learning, and their interaction have a significant positive impact on technological diversification; the innovation capacity and the uncertainty of the external environment also affect enterprises’ technological diversification.